What Does the Arctic’s Unstable Past Say about a Sustainable Future? - Henry P. Huntington (Sustainability, 2021)
Visions for tomorrow’s Arctic include complementary and conflicting ideas such as sustainability, security, prosperity, biodiversity, Indigenous rights, and more. Implicit in many of these views is the assumption that the right combination of policy and action will create a stable configuration producing the intended outcome for the foreseeable future. Even a cursory review of Arctic history, however, shows that economic, political, cultural, ecological, climatic, and other forms of stability are unlikely. Instead, the lessons of the past suggest that local and global factors will continue to interact to create high variability. Individual policies and institutions may help promote effective responses to that variability, but a commitment to enduring equity is necessary to foster long-term well-being for the Arctic and its peoples.